2005
DOI: 10.1074/jbc.m414678200
|View full text |Cite
|
Sign up to set email alerts
|

An Activation Switch in the Rhodopsin Family of G Protein-coupled Receptors

Abstract: We aimed at understanding molecular events involved in the activation of a member of the G protein-coupled receptor family, the thyrotropin receptor. We have focused on the transmembrane region and in particular on a network of polar interactions between highly conserved residues. Using molecular dynamics simulations and site-directed mutagenesis techniques we have identified residue Asn-7.49, of the NPxxY motif of TM 7, as a molecular switch in the mechanism of thyrotropin receptor (TSHr) activation. Asn-7.49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 46 publications
7
100
0
Order By: Relevance
“…1a, color corresponds to each substitution). Indeed, as reported before, all these point mutations caused an increase in basal cyclic AMP accumulation that, when normalized to the level of expression of each mutant allows sorting them according to their 'specific constitutive activity' 35 (Fig. 1b).…”
Section: Constitutively Active Tshr Mutants and Cooperativitysupporting
confidence: 64%
See 3 more Smart Citations
“…1a, color corresponds to each substitution). Indeed, as reported before, all these point mutations caused an increase in basal cyclic AMP accumulation that, when normalized to the level of expression of each mutant allows sorting them according to their 'specific constitutive activity' 35 (Fig. 1b).…”
Section: Constitutively Active Tshr Mutants and Cooperativitysupporting
confidence: 64%
“…Concentration-effect curves were fitted with Prism v5.0 and EC 50 calculated. Specific constitutive activity was calculated exactly as described previously 35 , based on the linear relationship existing between basal cAMP accumulation and receptor surface expression.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The XPKXY motif has been considered as a key motif equivalent to the well characterized NPXXY motif in family 1 GPCRs (27). In the case of glycoprotein hormone receptor, Thr 6.43 and Asp 6.44 interact mainly with Asn 7.49 in the NPXXY motif to keep the receptor inactive (31,32), and naturally occurring constitutively active mutations at these loci cause genetic disorders such as hyperfunctioning thyroid adenoma and familial male-limited precocious puberty (6). Moreover, the recent crystal structure of constitutively active mutant M257Y 6.40 of rhodopsin showed that elevation of the basal activity originated from the formation of specific interactions among helices III, V, VI, and VII including M257Y…”
Section: Similarity and Difference Between Xpkxy Motif And Npxxymentioning
confidence: 99%